Corporate Culture And Career Development On Employee Performance At BJB Syari’ah Cabang Bandung - Jaja Jaja (SINTESA, 2022)
The purpose of this study was to determine and analyze the influence of corporate culture and career development to employee performance in Bank bjb Sharia Branch Office Bandung, by knowing which one is more dominant variable affecting employee performance. Methods of data collection is done with interviews, questionnaires, and documentation. Model analysis of the data used is multiple linear regression analysis. Hypothesis testing simultaneously or partially performed using SPSS software version 18. The results showed that the corporate culture and career development simultaneously or partially significant effect on the performance of employees at the Bank bjb Sharia Branch Office Bandung. This means that the dependent variable is the employee's performance can be explained by the independent variables corporate culture and career development is 83.8%. While the remaining 16.2% is explained by other independent variables that are not included in this research model.